Developing MATCA as an offline Articulate Storyline-based interactive learning application for teaching light in elementary IPAS (IAIN Kendari, 2026)
Interactive digital media are increasingly needed to support elementary students’ understanding of abstract science concepts. This study aimed to develop MATCA, an offline Articulate Storyline-based interactive learning application for teaching light in fifth-grade elementary IPAS, and to examine its feasibility and practicality. The study employed a research and development design using the ADDIE model. Data were collected through needs analysis, expert validation sheets, and teacher and student response questionnaires. The developed application contains user instructions, learning competencies, structured materials, animated learning videos, and interactive quizzes. The feasibility assessment showed that MATCA was rated very feasible by the material expert with a score of 86% and by the media expert with a score of 83%. Student responses indicated very high practicality, with 100% for display and 95.35% for operation, while the teacher response reached 100% for both aspects. These findings indicate that MATCA is pedagogically feasible and practically usable as an offline interactive learning medium. The product offers an accessible digital learning alternative for elementary science instruction, although further studies are needed to examine its effectiveness in improving learning outcomes. Keywords: Articulate Storyline; elementary science learning; interactive learning media; IPAS; light concept; offline Android application